Experimental Estimation of Immunomodulating Activity of Tubosan, a New Russian Synthetic Drug - N. K. Chernikova; V. V. Mikhailov; S. V. Borisevich (Антибиотики и Химиотерапия)
Tubosan, a new Russian immunostimulator is a derivative of sulfopyrimidine. It stimulated the humoral antiviral immunity in mice, provoked increasing the number of the antibody forming cells in the spleen of mice, immunized by sheep's erythrocytes, and increased the titers of the virus-neutralizing antibodies after immunization by inactivated and live vaccines VEE. The Tubosan ability to lower the reactogenicity of the live VEE vaccine provided new perspectives for using such immunomodulators in medical practice.